Mahar Pernikahan menurut Hukum Adat Suku Bugis di Polewali Mandar sebagai Perbuatan Hukum Peralihan Hak Atas Tanah - Firdaus, Nurul; Djaja, Benny (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Mahar is an integral component of the marriage ceremony in the Bugis tribe. This dowry, given by the groom to the bride, serves as a source of livelihood for the married couple. In Bugis marriages, there are terms such as Panaiq money (wedding reception funds) and dowry or sompa money. Legally, both are considered gifts or grants given without expectation of return. These gifts may consist of movable assets such as money, gold, prayer sets, or vehicles, or immovable assets such as ricefields, gardens, ponds, houses, and coconut trees. Typically, immovable assets, especially land, are transferred as gifts through customary oral agreements or written grant letters, rather than formal deeds. This study employs literature review and interviews, with primary data derived from the Polewali District Court decision Number 32/Pdt.G/2024/PN Pol concerning a land grant dispute as a wedding gift. The court ruled in favor of the defendant, who possesses an authentic deed in the form of a will.